Comparative analysis of the economic and financial indicators applied to the manufacturing industries listed on the BOVESPA (Revista Brasileira de Contabilidade e Gestão, 2016)
The present research aimed to identify which economic-financial indices are most important for monitoring the managers of the Manufacturing Industry sector and, consequently, their relevance to their segments. For that, the factor analysis technique was used in the indicators extracted from the financial statements, which are sources of measurement of the companies' economic-financial performance. Twenty-four indices were selected, collected through the Economática® database, of companies with shares traded on BOVESPA in the period from 2004 to 2008. The results of the factor analysis showed that the relevant indices for the manufacturing sector are grouped into seven factors with power explanation of 77% of the data variability. The research also showed that there are no significant differences between the measurement characteristics of the indexes of the Manufacturing Industry sector and its specific segments.
Keywords: financial economic indicators; operating cycle; factor analysis; manufacturing industry; operating leverage